TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENGOPLOSAN GAS LPG SUBSIDI DI KABUPATEN KARAWANG - Saskia Falika Khaulah; Deny Guntara; Muhamad Abas (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
The criminal act of mixing subsidized LPG gas constitutes a misuse of subsidized energy distribution, which negatively impacts both society and the state’s finances. This study aims to juridically examine the elements of the criminal offense in the case of subsidized LPG mixing based on the Decision of the Karawang District Court Number 352/Pid.Sus-LH/2024/PN Kwg, as well as to assess the extent to which the decision reflects the principles of justice, legal certainty, and legal utility. The method used is normative legal research with statutory, conceptual, and case approaches. The results of the study indicate that the elements of the criminal offense in the case have been fulfilled, and the judges imposed criminal sanctions on the defendants. The decision is considered to have fulfilled the principles of legal certainty and justice; however, it has not been optimal in providing legal utility, as the relatively light punishment may reduce the deterrent effect and open up the possibility for similar offenses to occur in the future. Therefore, stricter law enforcement is necessary to prevent the recurrence of such cases.